Web and android-based application for monitoring tuberculosis (TB) patients in Kediri City - Toga Aldila Cinderatama; Ashafidz Fauzan Dianta; Fery Sofian Efendi; Kunti Eliyen (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2021)
Tuberculosis (TB) is a chronic disease that is still a public health problem globally, including Indonesia, due to its easy transmission. Treatment for TB sufferers consist of several drug combinations that are intended to eradicate germs. For TB sufferers, the key to successful treatment is the patient's compliance with taking medication every day. The lengthy treatment time is usually at least six months allowing non-adherence to taking the medication by the patient. If not treated properly, there will be a risk of disease complications, such as tuberculosis bacteria resistant to drugs, making TB treatment more difficult. In this study, an Android-based was built to remind TB sufferers to take their medication during the treatment process. In addition to the mobile-based application, there is also a web application used by drug drinking supervisors (PMO; Petugas Minum Obat in Indonesia) in monitoring TB patients, where the application can also view patient compliance statistics in taking medication and historical data on TB patients’ medical treatment. After completion and development, the application will be given to PMO officers and patients to be tested. It is hoped that the application can help the TB treatment process become more effective and prevent treatment failure from the implementation.